DIFFERENCES OF NEWCASTLE DISEASE ANTIBODY TITER IN ONE DAY AND SEVEN DAY VACCINATE BROILER - Permatasari, Dwi Arum; Suardana, Ida Bagus Kade; Nindhia, Tjokorda Sari (Buletin Veteriner Udayana, 2022)
Newcastle Disease (ND) is a disease caused by avian Paramyxovirus type-1. Common symptoms had seen early in infection are decreased appetite, lethargy and conjunctivitis. The main strategy that can be done to prevent the emergence of ND disease is by implementing a biosecurity system and vaccination, the success of vaccination is supported by post-vaccination antibody titer examination. This study aims to compare the determination of Newcastle Disease antibody titers in broiler vaccinated at the age of one day at the factory and seven days old.This study used 30 broiler divided into three treatment groups. The first sample chickens group were not vaccinated or known as control samples (P0). The second group of chickens has vaccinated one-day ages at the factory (P1). The third group of vaccinated chickens was seventh days old (P2). Blood sampling in the P0 group was carried out starting at the age of 7, 14, 21, 28 and 35 days, the P1 group at the age of 7, 14 and 21 days and in the P2 group at the age of 14, 21 and 28 days at random (random sampling) through the brachial vein. The examination of serum antibody titers can be using the Haemagglutination Inhibition (HI) serological test. The data obtained from the serological examination  results were analyzed using the statistical test of variance and regression analysis test SPSS software. The results showed that there was a significant difference in ND antibody titers in the first and second weeks after vaccination and there was no significant difference in the third week after vaccination. It is necessary to booster broilers vaccinated one day at the age of 13 days and broilers vaccinated at seven days at the age of 25 days to increase immunity again.